Ethical Consumption as an Indicator and Resource of Civil Society Transformation in Russia - Marina Shabanova (Journal of Economic Sociology, 2025)
This paper substantiates a theoretical concept and tests hypotheses concerning the relationship between ethical consumption as a new sphere of civil society (CS) and its traditional sphere (formal and informal structures beyond the consumption sphere). This paper, for the first time, presents data on Russians’ participation in a wide range of ethical consumption practices in different markets and stages of dealing with benefits (acquisition, utilization and disposal), based on the results of two representative studies conducted in 2020 and December 2022 (N = 2,000 for each study). It has been established that, although different practices are favored differently, Russian citizens, for the most part, have already been using them. Without due regard to this multifaceted phenomenon, the notion of modern CS,—its functions and resources—remains deficient. Based on an analysis of the extent of overlapping participants in different practices, considerable fragmentation (disconnect) within this phenomenon was revealed, both within specific types and among them. This fragmentation reduces the contribution of ethical consumption to advancing sustainable development, although its contribution to the development of CS remains positive in any case. The emergence of ethical consumption has been shown to signal the development of Russian CS both in depth (owing to acquisition of a new sphere for demonstrating civic consciousness by those who have already been involved in traditional civic structures—formal and informal) and in breadth (owing to the inflow of new participants who were socially passive before). Using regression analysis, the relationship between specific factors and the probability of Russians’ involvement in different types of ethical consumption was established and weaknesses in the development of the latter were revealed. It was concluded that an expanded reproduction of ethical consumption requires a variety of effects to be exerted by key stakeholders (NGOs, authorities, businesses) to make an impact on different categories of ethical consumers, different stages and kinds of ethical consumption, which would increase the contribution of this phenomenon to the development of CS in Russia.